(untitled) (Agro Productividad, 2026)
Objective: This study evaluated the residues from Pleurotus ostreatus mushroom cultivation as a potential alternative feed source for ruminants. Design/Methodology/Approach: A completely randomized design was implemented with three treatments corn, oats, and sorghum each replicated four times. The physicochemical properties of the agricultural residues were analyzed both before and after mushroom cultivation. Parameters measured included dry matter (DM), crude protein (CP), ether extract (EE), ash (A), neutral detergent fiber (NDF), and in vitro digestibility. Statistical analyses were performed using the InfoStat software. Results: Sorghum and oat residues exhibited higher carbon concentrations, whereas corn residues contained the greatest amount of NDF. Post-cultivation analysis revealed that oat residues presented an NDF content of 72.62%, exceeding that of corn and sorghum. Moreover, EE content increased in corn and sorghum residues, reaching 2.07% and 2.16%, respectively. A notable rise in CP was observed in oat residues, which reached 10.2%. In terms of in vitro digestibility, corn stover demonstrated the highest digestibility at 45 hours (65%), while oat stover exhibited the lowest. Limitations/Implications: Identifying nutritionally rich and sustainable feed alternatives for ruminants remains critical to ensuring year-round availability and reducing dependency on conventional feed sources. Findings/Conclusions: Residues derived from mushroom cultivation represent a promising nutritional resource for ruminant diets, particularly due to their enhanced protein and lipid profiles.